Establishment and Application of a Dual-Labeling Time-Resolved Fluorescence Immunoassay Method for Simultaneous Detection of the Troponin I-C Complex and Full-Size-Troponin I - Biao Huang; Jian Wu; Jian Wu; Hao Chen; Li Zhang; Xiumei Zhou; Qingqing Wu; Ting Li; Yigang Wang; Penguo Xia; Yaping Dai; Guoyin Kai; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The measurement of cardiac troponin I (cTnI) is widely used in the diagnosis of acute myocardial infarction (AMI). Although existing cTnI detection methods measure total cTnI, the significance of undegraded full-size-cTnI levels is still not well-understood. In this study, we have established a novel dual-labeling time-resolved fluorescence immunoassay (TRFIA) technique that simultaneously detects the cTnI-C complex and full-size-cTnI, allowing us to explore the clinical value of full-size-cTnI determination.Methods: An antibody against the 23–43 amino acid region of cTnI protected by endogenous cTnC is coupled to magnetic beads to provide a solid-phase antibody for capturing all cTnI. An antibody against cTnC in the cTnI-C complex labeled with Eu3+ was used to detect the cTnI-C complex, and an antibody labeled with Sm3+ near the C-terminal 190–203 amino acids of cTnI was used to detect full-size-cTnI. Through dual-labeling TRFIA, cTnI-C complex, full-size-cTnI, and the full-size-cTnI/cTnI-C ratio can be detected simultaneously. The dual-labeling TRFIA technique was used to analyze serum samples collected at different times during treatment and compare their full-size-cTnI/cTnI-C ratios.Results: The sensitivity for the cTnI-C-TRFIA complex was 0.02 ng/mL, the measurement range was 0.02–40 ng/mL, the average intra-batch coefficient of variation (CV) was 4.35%, and the inter-average CV was 6.23%. The correlation coefficient between cTnI-C-TRFIA and commercial cTnI-CLIA methods was R2 = 0.8887. The sensitivity for full-size-cTnI-TRFIA was 0.04 ng/mL, the measurement range was 0.04–40 ng/mL, the average intra-batch CV was 4.95%, and the average inter-batch CV was 7.79%. The correlation coefficient between full-size-cTnI-TRFIA and commercial cTnI-CLIA methods was R2 = 0.7247.Conclusions: Dual-labeling full-size-cTnI/cTnI-C-TRFIA analysis is helpful for determining the length of time of chest pain before admission and the degree of continuous release of cTnI in the myocardium. Thus, it is more for early prognosis than just detecting cTnI.